Amyloidosis cutis dyschromica, a rare cause of hyperpigmentation: a new case and literature review - Kuseyri Hübschmann, Oya; Haas, Dorothea; Lang, Nina; Schäkel, Knut; Bettendorf, Markus (Pediatrics, 2017)
Amyloidosis cutis dyschromica is a rare form of primary cutaneous amyloidosis without systemic involvement and characterized by asymptomatic, progressive hyper- and hypopigmentation. We present the first case of a patient with amyloidosis cutis dyschromica diagnosed previously elsewhere as having Addison disease with generalized hyperpigmentation of the skin. This case suggests that in patients presenting with asymptomatic cutaneous dyschromia a skin biopsy for histopathological examination should be considered.
Gesehen am 31.10.2018